PROSES PENERIMAAN DIRI PADA INDIVIDU YANG MENGALAMI SURVIVOR'S GUILT AKIBAT PANDEMI COVID-19 - Maria Yosephin; Eunike Sri Tyas Suci (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2022)
The COVID-19 pandemic has a broad impact on society. The high death rate from COVID-19 canmake individuals feel guilty when dealing with the loss of loved ones. This study aimed to explorethe process of self-acceptance in individuals who experience survivor's guilt due to the COVID-19pandemic. This study used a phenomenological method. The participants in this study were threeyoung adults 18-39 years old who were still in the process of overcoming survivor's guilt. Theresults showed that the three participants felt regret, helplessness, anger and sadness because theyhave a healthier and more secure condition, while their loved ones are not safe. They tended toblame themselves (survivor's guilt) for something that did not directly affect the death of theirparents. The process of self-acceptance experienced by the participants is unique and non-linearrelated to the aspects of aversion, curiosity, tolerance, allowing and friendship. Emotionalprocesses, participant perceptions, religiosity and support from the environment are factors thatinfluence the process of self-acceptance of the three participants.